(untitled) (Journal of Student Affairs in Africa, 2021)
The purpose of the article is to trace the development of student unionism in Zimbabwe. On the basis of a discussion of the nature of the university, the article argues that because the university environment tolerates and promotes academic freedom and liberal values, it provides an environment conducive to critical thought and oppositional politics, while the university quite often itself becomes the target for student attack. Student representation during the pre-independence period in Zimbabwe sought to engage the institution in its effort to re-order society at a time of racial struggle and class conflict. After independence, student representation was in support of government efforts to create a better Zimbabwe and to consolidate the gains of independence. However, after the first decade of independence, the relationship between students and government soured due to students’ opposition to the one-party system as well as the University of Zimbabwe Amendment Bill, among other issues. This article thus documents and analyses the relationship between students and government with reference to three periods and two key moments: the 1973 protests against racial discrimination in the pre-independence phase and the post-1990 developments in Zimbabwean national and university politics.